Monkeys can identify pictures from words. - Elizabeth Cabrera-Ruiz; Marlen Alva; Mario Treviño; Miguel Mata-Herrera; José Vergara; Tonatiuh Figueroa; Javier Perez-Orive; Luis Lemus (PLoS ONE)
Humans learn and incorporate cross-modal associations between auditory and visual objects (e.g., between a spoken word and a picture) into language. However, whether nonhuman primates can learn cross-modal associations between words and pictures remains uncertain. We trained two rhesus macaques in a delayed cross-modal match-to-sample task to determine whether they could learn associations between sounds and pictures of different types. In each trial, the monkeys listened to a brief sound (e.g., a monkey vocalization or a human word), and retained information about the sound to match it with one of 2-4 pictures presented on a touchscreen after a 3-second delay. We found that the monkeys learned and performed proficiently in over a dozen associations. In addition, to test their ability to generalize, we exposed them to sounds uttered by different individuals. We found that their hit rate remained high but more variable, suggesting that they perceived the new sounds as equivalent, though not identical. We conclude that rhesus monkeys can learn cross-modal associations between objects of different types, retain information in working memory, and generalize the learned associations to new objects. These findings position rhesus monkeys as an ideal model for future research on the brain pathways of cross-modal associations between auditory and visual objects.